Algebra


  1. If  
    a
    =
    c
    =
    e
    = 3,then
    2a2 + 3c2 +4e2
      = ?
    bdf2b2 + 3d2 + 4f2









  1. View Hint View Answer Discuss in Forum

    a
    =
    c
    =
    e
    = 3
    bdf

    ⇒  a = 3b ; c = 3d ; e = 3f
    ∴ 
    2a2 + 3c2 +4e2
    2b2 + 3d2 + 4f2

    =
    2 × 9b2 + 3 × 9d2 + 4 × 9f2
    2b2 + 3d2 + 4f2

    =
    9(2b2 + 3d2 +4f2)
    = 9
    2b2 + 3d2 + 4f2

    Correct Option: D

    a
    =
    c
    =
    e
    = 3
    bdf

    ⇒  a = 3b ; c = 3d ; e = 3f
    ∴ 
    2a2 + 3c2 +4e2
    2b2 + 3d2 + 4f2

    =
    2 × 9b2 + 3 × 9d2 + 4 × 9f2
    2b2 + 3d2 + 4f2

    =
    9(2b2 + 3d2 +4f2)
    = 9
    2b2 + 3d2 + 4f2


  1. If a, b, c are real and a2 + b2 + c2 = 2 (a – b – c) – 3, then the value of 2a – 3b + 4c is









  1. View Hint View Answer Discuss in Forum

    a2 + b2 + c2 = 2a – 2b – 2c – 3
    ⇒  a2 – 2a + b2 + 2b + c2 + 2c + 1 + 1 + 1 = 0
    ⇒  (a2 – 2a + 1) + (b2 + 2b + 1) + (c2 + 2c + 1) = 0
    ⇒  (a – 1)2 + (b + 1)2 +(c + 1)2 = 0
    ⇒  a – 1 = 0 ⇒ a = 1
    ⇒  b + 1 = 0 ⇒ b = –1
    and c + 1 = 0 ⇒ c = –1
    ∴  2a – 3b + 4c = 2 + 3 – 4 = 1

    Correct Option: C

    a2 + b2 + c2 = 2a – 2b – 2c – 3
    ⇒  a2 – 2a + b2 + 2b + c2 + 2c + 1 + 1 + 1 = 0
    ⇒  (a2 – 2a + 1) + (b2 + 2b + 1) + (c2 + 2c + 1) = 0
    ⇒  (a – 1)2 + (b + 1)2 +(c + 1)2 = 0
    ⇒  a – 1 = 0 ⇒ a = 1
    ⇒  b + 1 = 0 ⇒ b = –1
    and c + 1 = 0 ⇒ c = –1
    ∴  2a – 3b + 4c = 2 + 3 – 4 = 1



  1. If a, b, c are real and a2 + b2 + c2 = 2 (a – b – c) – 3, then the value of 2a – 3b + 4c is









  1. View Hint View Answer Discuss in Forum

    a2 + b2 + c2 = 2a – 2b – 2c – 3
    ⇒  a2 – 2a + b2 + 2b + c2 + 2c + 1 + 1 + 1 = 0
    ⇒  (a2 – 2a + 1) + (b2 + 2b + 1) + (c2 + 2c + 1) = 0
    ⇒  (a – 1)2 + (b + 1)2 +(c + 1)2 = 0
    ⇒  a – 1 = 0 ⇒ a = 1
    ⇒  b + 1 = 0 ⇒ b = –1
    and c + 1 = 0 ⇒ c = –1
    ∴  2a – 3b + 4c = 2 + 3 – 4 = 1

    Correct Option: C

    a2 + b2 + c2 = 2a – 2b – 2c – 3
    ⇒  a2 – 2a + b2 + 2b + c2 + 2c + 1 + 1 + 1 = 0
    ⇒  (a2 – 2a + 1) + (b2 + 2b + 1) + (c2 + 2c + 1) = 0
    ⇒  (a – 1)2 + (b + 1)2 +(c + 1)2 = 0
    ⇒  a – 1 = 0 ⇒ a = 1
    ⇒  b + 1 = 0 ⇒ b = –1
    and c + 1 = 0 ⇒ c = –1
    ∴  2a – 3b + 4c = 2 + 3 – 4 = 1


  1. If for non-zero, x, x2 – 4x – 1 = 0, the value of x2 +
    1
      is
    x2









  1. View Hint View Answer Discuss in Forum

    x2 – 4x – 1 = 0
    ⇒  x2 –1 = 4x
    Dividing by x

    x −
    1
    = 4
    x

    On squaring both sides,
    x −
    1
    2 = 16
    x

    ⇒  x2 +
    1
    – 2 = 16
    x2

    ⇒  x2 +
    1
    = 16 + 2 = 18
    x2

    Second Method :
    Using Rule 5,
    Here, x2 – 4x – 1 = 0
    ⇒  x2 – 1 = 4 x
    ⇒  x2
    1
    = 4
    x

    We know that
    x2 +
    1
    = x −
    1
    2 + 2
    x2x

    = 42 + 2 = 18

    Correct Option: D

    x2 – 4x – 1 = 0
    ⇒  x2 –1 = 4x
    Dividing by x

    x −
    1
    = 4
    x

    On squaring both sides,
    x −
    1
    2 = 16
    x

    ⇒  x2 +
    1
    – 2 = 16
    x2

    ⇒  x2 +
    1
    = 16 + 2 = 18
    x2

    Second Method :
    Using Rule 5,
    Here, x2 – 4x – 1 = 0
    ⇒  x2 – 1 = 4 x
    ⇒  x2
    1
    = 4
    x

    We know that
    x2 +
    1
    = x −
    1
    2 + 2
    x2x

    = 42 + 2 = 18



  1. The value of  
    4 + 3√3
      is
    7 + 4√3









  1. View Hint View Answer Discuss in Forum

    Expression =
    4 + 3√3
    7 + 4√3

    Rationalising the denominator,
    =
    (4 + 3√3)(7 − 4√3)
    (7 + 4√3)(7 − 4√3)

    =
    28 − 16√3 + 21 √3 − 12 × 3
    49 − 48

    = 28 + 5√3 – 36 = 5√3 – 8

    Correct Option: A

    Expression =
    4 + 3√3
    7 + 4√3

    Rationalising the denominator,
    =
    (4 + 3√3)(7 − 4√3)
    (7 + 4√3)(7 − 4√3)

    =
    28 − 16√3 + 21 √3 − 12 × 3
    49 − 48

    = 28 + 5√3 – 36 = 5√3 – 8